LES RUPTURES UTERINES A L’HOPITAL DE REFERENCE DE PARAKOU AU BENIN : ASPECTS EPIDEMIOLOGIQUES, THERAPEUTIQUES ET PRONOSTIQUES - Kabibou, Salifou; Sambo, Bio Tamou; Tchaou, Blaise Adelin; Sidi, Rachidi; Dénakpo, Justin; Lokossou, Antoine; Perrin, René-Xavier (European Scientific Journal, ESJ, 2015)
Objective: To describe the epidemiological, therapeutic and prognostic of uterine rupture in a second-level referral hospital in Parakou in Benin. Patients and methods: This was a descriptive cross-sectional study from a comprehensive sampling. It covered a period of 14 years (1 January 2001 to 31 December 2014) and involved 203 patients. Results: The frequency of uterine rupture in service was 0.7%, a uterine rupture for 135 deliveries. These were the patients referred in 77.3% of cases. The average age of these patients was 28 ± 5.4 years, ranging from 13 to 44 years. The etiologic factors were often associated. It was basically multiparity (42.4%), obstructed labor (32%) and uterine scars (26.1%). Treatment was conservative in 85.7%. The average time of surgical management was 01h38min ± 42min. In 69.8% of cases, patients were transfused and 72, 3% of the patients had received intravenous fluids. The prognosis is characterized by high perinatal mortality (80.2%) and maternal morbidity is dominated by anemia (79.7%) and abscesses (9.7%) and fistulas (2.4%). Conclusion: The epidemiological aspects of uterine ruptures in the gynecology and obstetrics department of CHD B encourage us to family planning, screening of dystocia and management deliveries on uterus scar.